2007
DOI: 10.1038/sj.bjc.6603710
|View full text |Cite
|
Sign up to set email alerts
|

Predictive factors associated with prolonged survival in patients with advanced non-small-cell lung cancer (NSCLC) treated with gefitinib

Abstract: This study aimed to identify predictive factors associated with prognostic benefits of gefitinib. A total of 221 Japanese patients who received gefitinib (250 mg day À1 ) were examined retrospectively and potential predictive factors analysed. Overall response rate (ORR) was 24.4% and median survival time (MST) was 8.0 months. In a log-rank test, survival was significantly better in females, patients with adenocarcinoma, never-smokers, favourable performance status (PS) and patients with epidermal growth facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
37
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 29 publications
4
37
0
Order By: Relevance
“…The incidence of EGFR mutations in this study (15%) was consistent with Western (13) and other Korean data (11,12), although lower than that reported in the previous studies from Taiwan and Japan (14,15). Our result should be interpreted with caution because it represents only a small group of patients with advanced NSCLC, and the patients had unfavorable clinical characteristic.…”
Section: Discussionsupporting
confidence: 78%
“…The incidence of EGFR mutations in this study (15%) was consistent with Western (13) and other Korean data (11,12), although lower than that reported in the previous studies from Taiwan and Japan (14,15). Our result should be interpreted with caution because it represents only a small group of patients with advanced NSCLC, and the patients had unfavorable clinical characteristic.…”
Section: Discussionsupporting
confidence: 78%
“…(4,(10)(11)(12)20,22,24,26,27,(32)(33)(34)(35)(36) The prevalence of EGFR mutations in our Japanese cohort was low (18%) compared with values determined previously for East Asian populations. Given that most previous studies examined only individuals treated with EGFR TKI, patient selection based on clinical predictors might have led to an increase in the proportion of subjects with adenocarcinoma histology, a factor known to be associated with EGFR mutations.…”
Section: Discussionmentioning
confidence: 88%
“…Two well conducted retrospective reports from the Dana-Farber/Harvard Cancer Center (DF/HCC) [52] and the Memorial Sloan-Kettering Cancer Center [53] combining 32 (22 exon 19 deletions, and 10 L858R) and 34 patients (23 exon 19 deletions, and 11 L858R), respectively, indicated that the response rates, progression-free and overall survival of gefitinib or erlotinib treated individuals was superior in exon 19 deletions than the L858R mutation patients [52,53]. Two retrospective East Asian cohorts did not show significant differences in survival between the gefitinib-treated L858R and exon 19 deletions [25,28,50], and a recent Japanese retrospective report actually described an improved survival for L858R-bearing patients after gefitinib therapy [54].…”
Section: Discussionmentioning
confidence: 99%